Management of scientific research at Tra Vinh University - Nguyen Van Sau (Southern Leyte State University, 2020)
Scientific research management is a core activity of the university, an activity established at the level of the organization, to find ways to add value to the research activities of academic staff. It plays an important role in the research processes that leads to technology transfer, brokerage and knowledge sharing, scientific cooperation, success, and productivity. It is research that helps build unique knowledge based on leadership and management practices and developing leaders and effective management. This study is based on the Research Management Model of Jan-Hendrik Schretlen (2014). The objective of the study is to understand research management at the organizational level in the schools of Tra Vinh University. The status of current research managers on scientific research management inputs such as personnel, policies, budgets, facilities, and priorities that meet requirements, are evaluated from advance or more. Findings revealed that management aspects, management tasks, management skills, management structure, and management tools are highly appreciated by schools. Also, there is an inverse correlation between performance and research management, an inverse correlation between citation and management tasks, between citation with the management structure. The management structure and management tasks have a negative impact on the citation. There are differences between schools in management efficiency, schools with academic strengths, and research as diverse fields of organizational resources and implementation of knowledge management to apply standards. On that basis, a series of recommendations for the implementation of this revolutionary scientific research management has been provided.